A new distributional record of the rare bat Coelops robinsoni from Sarawak, Malaysian Borneo. - Mohd Ridwan, Abd Rahman; Anang Setiawan, Achmadi; Roberta Chaya, Tawie Tingga; Noor Haliza, Hasan (Journal of Tropical Biodiversity Conservation, 2010)
A specimen of the rare Lesser Tailless Roundleaf Bat, Coelops robinsoni was caught at the mouth of Lobang Gan Kira, one of the entrances to Niah Cave, Niah National Park (NNP) on 15th November 2008. This bat is a new record for the park and only the third record for Malaysian Borneo, the previous records being from the Deer Cave, Mulu and Sarawak Planted Forest Zone (SPFZ), Bintulu Division. Detailed descriptions of the external morphology, skull and dentition are presented. Additional individuals of this species may occur in the cave as a potential roosting site was found on the cave ceiling approximately six meters above the floor and 300m from the entrance. More information on this bat is crucial for immediate and effective conservation plans as this species is listed as vulnerable by the IUCN.